PENINGKATAN NILAI GIZI ROTI TAWAR BERBASIS TERIGU DAN MOCAF DENGAN FORTIFIKASI TEPUNG WORTEL - Gian Kiswari; Eko Basuki; Siska Cicilia (The Journal of Teknologi Pangan, 2023)
This study aims to determine the effect of carrot flour fortification in the making of white bread on nutritional value, physical and organoleptic properties. The method used was experimental in the laboratory with the treatment of wheat flou:mocaf: fortification of carrot flour (W) namely of W1 (100:0:0%), W2 (70:28:2%), W3 (70:26:4%), W4 (70:24:6%), W5 (70:22:8%), dan W6 (70:20:10%). Parameters tested were nutritional value (antioxidant activity, moisture, and ash content), physical properties (swelling volume) and organoleptic properties (taste, color, and texture). Observational data were analyzed using ANOVA and further testing using Honest Significant Difference (HSD) with a level of 5%. The results showed that carrot flour fortification had a significantly different effect on the nutritional value, physical properties, and organoleptic properties of white bread. Carrot flour fortification as much as 10% was recommended as the best treatment in improving the quality of white bread with actual antioxidant activity criteria of 92.10%; moisture content 34.27%; ash content of 2.13%, swelling volume of 53.73% and the taste organoleptic properties were favored by panelists